TEKNOLOGI REDUKSI EMISI GAS RUMAH KACAPADA BUDIDAYA PADI SAWAH INDONESIA - Wentasari, Risa; Lisa, Irma (University of Prof. Dr. Hazairin, SH, 2024)
The aim of this research is to provide information on the development of research results regarding technology in reducing greenhouse gas emissions in lowland rice cultivation in Indonesia. The method used is a narrative review with a limit of taking articles from 2003 – 2023. The results of the literature review of the articles obtained were grouped into five categories of technology types, namely low emission varieties, land processing, soil fertility management, irrigation management, use of greenhouse gas reducing bacteria. The information obtained in each category is still limited and does not yet describe integrated cultivation technology in reducing greenhouse gases. From this research, it is recommended that research development related to low greenhouse gas varieties, land processing, recommendations for organic and inorganic fertilization, irrigation and the use of greenhouse gas reducing bacteria still need to be carried out in order to achieve the target of reducing greenhouse gas emissions in Indonesia.